Poster: A Dynamic Task Scheduling using Multi-Platoon Architecture in Vehicular Networks - Xiao, Tingting; Chen, Chen; Pei, Qingqi; Wan, Shaohua (Proceedings of the International Conference on Distributed Computing Systems, 2022)
The autonomous vehicle platoon has the potential to cope with the stress caused by the resource-constrained vehicles' demand for processing power and the spread-out deployment of MEC-BS. In this poster, we focus on a multi-platoons scenario for task scheduling. Our objective is to minimize the overall energy consumption subject to the long-term latency constraint. To characterize stochastic properties and deal with coupling between variables, we propose a dynamic task scheduling algorithm based on Lyapunov optimization (LDTS). We theoretically and empirically evaluate the performance of the proposed algorithm, which is illustrated to be significantly better than state-of-the-art and other benchmark approaches in terms of execution latency and energy consumption.